CLINICAL RESEARCH:Determinants of awareness, treatment and control of hypertension in Isfahan, Central Iran - Ramezani, Mohammad A.; Dastanpour, Maasoomeh; Eshaghi, Seyed R.; Fadaee-Nobari, Reza; Heydari, Kamal (Archives of Medical Science, 2009)
Introduction: Prevalence, awareness, treatment, and control rates of hyper-tension (HTN) are essential and considerable in health promotion and policy. The purpose of this study was to assess hypertension prevalence, awareness, treatment and control rates in the Iranian general population and determine their associated factors. Material and methods: We selected samples from a national survey named Non-Communicable Disease Risk Factors Surveillance that was designed by the Health Ministry – Center of Disease Control – Iran. The evaluation was done based on the WHO stepwise approach for non-communicable disease (NCD) risk factors. Data were collected by survey and registered clinical assessment by health professionals in a special survey questionnaire in Isfahan district area. At the end data were analyzed by logistic regression. Results: The overall prevalence of high BP was 20.7% (95% CI = 19.4-22). Of these, 59.7% were aware, 31.1% of hypertensives were receiving treatment, and 6.2% controlled. Multivariate analysis showed that old age (45-54 years OR = 7.5 (95% CI: 2.2-25.6), 55-64 years OR = 7.9 (95% CI: 2.3-26.7) compared with 15-24 years), female sex (OR = 2.3 [95% CI: 1.6–3.4] vs. male), urbanization (OR = 1.8 [95% CI: 1.02-2.2] compared with rural) and high waist circumference (WC) (OR = 1.8 [95% CI: 1.2-2.8] compared with low WC) were independently associated with higher BP awareness. No significant factor was associated with treatment of HTN. The only factor that affected HTN control was high WC (OR = 3.1 95% CI: 1.6-6). Conclusions: The awareness of patients about HTN was high but the treatment and control of it was not adequate. Determination of factors associated with them is necessary for control of HTN.